Case study of an energy-intensive consumer - Tavares, Inês Vieira (Neutro à Terra, 2021)
The energy sector is one of the pillars of growth and development for industries and it has been increasing in the last decades. Due to the need of rationalizing energy in industries, the concept of energy efficiency arises. For a rational use of energy, it was created strategies and measures to reduce energy consumptions in a sustainable way – social, economic and environmental. To analyze these consumptions, this paper contains a case study of an energy intensive industrial installation. This study consists of analyzing all the energy consumptions of the installation, through the obtained values of energy indicators.